1999
DOI: 10.1128/aem.65.8.3293-3297.1999
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Diversity of Archaea in Heavy-Metal-Contaminated Soils

Abstract: The impact of heavy-metal contamination on archaean communities was studied in soils amended with sewage sludge contaminated with heavy metals to varying extents. Fluorescent in situ hybridization showed a decrease in the percentage of Archaea from 1.3% ± 0.3% of 4′,6-diamidino-2-phenylindole-stained cells in untreated soil to below the detection limit in soils amended with heavy metals. A comparison of the archaean communities of the different plots by denaturing gradient gel electrophoresis revealed differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(51 citation statements)
references
References 36 publications
6
43
0
2
Order By: Relevance
“…The presence of members of the two major established archaeal kingdoms, Crenarchaeota and Euryarchaeota in nonthermophilic environments has been demonstrated by 16S rRNA gene surveys, with Crenarchaeota often more common in soil environments (Nicol et al, 2003). In particular, nonthermophilic 'Group I' Crenarchaeota have been reported in numerous environments including marine (Delong, 1992;Fuhrman et al, 1992) and freshwater environments (Jurgens et al, 2000), sediments (Hershberger et al, 1996;MacGregor et al, 1997;Schleper et al, 1997), bulk soil (Bintrim et al, 1997;Jurgens et al, 1997;Buckley et al, 1998;Sandaa et al, 1999;Ochsenreiter et al, 2003) and the rhizosphere and mycorrhizosphere (Simon et al, 2000;Bomberg et al, 2003). Estimates based on 16S rRNA gene copy numbers suggest that Crenarchaeota constitute 1-5% of the total prokaryotic community in soils (Buckley et al, 1998;Sandaa et al, 1999;Ochsenreiter et al, 2003), with some estimates as high as 12-38% (Kemnitz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of members of the two major established archaeal kingdoms, Crenarchaeota and Euryarchaeota in nonthermophilic environments has been demonstrated by 16S rRNA gene surveys, with Crenarchaeota often more common in soil environments (Nicol et al, 2003). In particular, nonthermophilic 'Group I' Crenarchaeota have been reported in numerous environments including marine (Delong, 1992;Fuhrman et al, 1992) and freshwater environments (Jurgens et al, 2000), sediments (Hershberger et al, 1996;MacGregor et al, 1997;Schleper et al, 1997), bulk soil (Bintrim et al, 1997;Jurgens et al, 1997;Buckley et al, 1998;Sandaa et al, 1999;Ochsenreiter et al, 2003) and the rhizosphere and mycorrhizosphere (Simon et al, 2000;Bomberg et al, 2003). Estimates based on 16S rRNA gene copy numbers suggest that Crenarchaeota constitute 1-5% of the total prokaryotic community in soils (Buckley et al, 1998;Sandaa et al, 1999;Ochsenreiter et al, 2003), with some estimates as high as 12-38% (Kemnitz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the dynamism of soil crenarchaeal communities in response to different environmental factors (e.g. Sandaa et al ., 1999;Nicol et al ., 2003a) and their apparent ubiquity but reduced complexity in comparison with bacterial communities make crenarchaea a useful target group when making comparisons between different environmental samples. Crenarchaea have been reported to constitute a significant proportion of soil prokaryotes ranging from 0.16% to 3% of 16S rRNA genes (Ochsenreiter et al ., 2003) and approximately 1% of hybridized whole cells (Sandaa et al ., 1999) or extracted 16S rRNA (Buckley et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Sandaa et al ., 1999;Nicol et al ., 2003a) and their apparent ubiquity but reduced complexity in comparison with bacterial communities make crenarchaea a useful target group when making comparisons between different environmental samples. Crenarchaea have been reported to constitute a significant proportion of soil prokaryotes ranging from 0.16% to 3% of 16S rRNA genes (Ochsenreiter et al ., 2003) and approximately 1% of hybridized whole cells (Sandaa et al ., 1999) or extracted 16S rRNA (Buckley et al ., 1998). Several studies have indicated that soil crenarchaea may have a specific association with plant roots (Großkopf et al ., 1998;Simon et al ., 2000;Chelius and Triplett, 2001) and crenarchaea may therefore play an important role in the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Roling et al (2004a) reported a negative effect on archaea by oil spills in beach sediments in laboratory experiments. Sandaa et al (1999) also observed a decrease in archaeal numbers with increasing heavy-metal contamination in soils. In this study, we found a dramatic decrease in in situ archaea in oil-contaminated soils as indicated by the limited archaeal genes on the array.…”
Section: Discussionmentioning
confidence: 75%